Enhancing an urban neighborhood’s collective efficacy through community garden design - Yeager, Mackenzie (Kansas State University, 2020)
Collective efficacy, which can be broken down to social cohesion and informal social control, is a crucial component in the healthy social life of urban neighborhoods. On a neighborhood level, collective efficacy correlates with shared community trust and the ability to speak out about crime or disorderly physical characteristics. Community gardens have been acknowledged for their collective efficacy building potential because they specifically promote collaboration and active participation, both of which are necessary for social cohesion and informal social control. Community gardens can vary greatly in size, function, location, and involvement making it unclear whether a community garden by itself is sufficient to enhance the surrounding residents’ collective efficacy or whether specific programming is needed. This project explores how a community garden can enhance collective efficacy in an urban neighborhood. Through community collaboration in a garden design process, the project examines the community garden environmental factors that can contribute to neighborhood-wide collective efficacy. It also analyzes the community’s ability to create their own collective efficacy through active design processes. The result is a projective community garden design that is intended to enhance collective efficacy in surrounding neighborhoods. Data from paper surveys, online surveys, and focus group sessions was collected over several weeks in the target area. Participants’ current collective efficacy levels were assessed as well as their opinions about the importance of certain community garden elements and ideas for future garden design. While community garden presence in a neighborhood was not always associated with higher collective efficacy, gardens that were multi-functional and met social needs were more likely to be associated with higher levels. Respondents that participate in community gardening for job training and inter-cultural communication reported the highest levels of collective efficacy, suggesting that the reason behind garden participation is significant. The data suggests that gardens with a diverse range of functions and participants are the most conducive to fostering neighborhood collective efficacy.
Keywords: Collective efficacy; Community gardening; Urban agriculture